Arabic for tourism purpose via web-based learning at MARA Poly-Tech College (KPTM) - Abdul Ghani, Mohammad Taufiq; Wan Daud, Wan Ab Aziz; Sahrir, Muhammad Sabri (2016)
This project presents an educational website for learning Arabic for tourism purposes for beginners that was specifically designed for diploma students that are non-Arabic native speakers at the MARA Poly-Tech College (KPTM). This website was designed by using Joomla ® as a platform for website development based on ADDIE instructional design model. The website was designed based on students’ needs, opinions, and suggestions, which was evaluated by the participants involved in this study among tourism students who studied Arabic language. The study found that the majority of the students were positive about learning the Arabic language for tourism purposes through the website which increases the students’ desire, motivates them to learn Arabic and gives them opportunities to practice self-learning.